Antecedents of intercultural adjustment of American expatriates in the People's Republic of China. - Hallet Hullinger; Robert Nolan (Adult Education Research Conference, 1997)
A greater understanding of the antecedents of intercultural adjustment of Americans working in China can assist organizations in selecting, training and supporting employees who work in this country. Interviews with forty Americans and seven Chinese living in Beijing yielded seven categories of adjustment factors labeled as personality, expectations, prior overseas experience, motivation, language skills, intra- and intercultural relationships, preparation and training. Four categories could be classified as endogenous, that is originating within the person, and three could be considered exogenous, that is originating within the environment.